2015
DOI: 10.1515/text-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

A corpus-based study of metaphor signaling variations in three genres

Abstract: This study examines the use of words and phrases that signal metaphors in three genres in order to further examine the corpus-based evidence for signaling variation mentioned in previous research. While previous studies have focused on pragmatic functions, discourse functions, and the level of conventionalization, this study demonstrates that the communicative goals within each genre underlie the reasons for the metaphor signaling. Three corpora of approximately 600,000 words were created for this research, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, scientific metaphors are typically used to convey topics that are ideationally troublesome to communicate (Cameron, 2003). Discursive studies of metaphor have identified their careful crafting for particular audiences especially when the topics or concepts are considered difficult to grasp (Pramling, 2010;Semino, 2008;Skorczynska & Ahrens, 2015). The lack of concern identified in the current study for an accurate relationship between target and source can be assumed to reflect the experts' understanding of their rights and obligations in the news interview settings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, scientific metaphors are typically used to convey topics that are ideationally troublesome to communicate (Cameron, 2003). Discursive studies of metaphor have identified their careful crafting for particular audiences especially when the topics or concepts are considered difficult to grasp (Pramling, 2010;Semino, 2008;Skorczynska & Ahrens, 2015). The lack of concern identified in the current study for an accurate relationship between target and source can be assumed to reflect the experts' understanding of their rights and obligations in the news interview settings.…”
Section: Discussionmentioning
confidence: 89%
“…These were examined for the pattern of their occasioning by experts or their response to metaphors that their interviewers introduced. Their marking was examined for signals (e.g., 'a kind of', or 'really') indicating that the vehicle term was presented to be interpreted more or less metaphorically (Goatly, 1997, Skorczynska & Ahrens, 2015. Vehicle terms were also examined for their clustering, replacing or modifying (Cameron & Stelma, 2004, Cameron, 2008 as well as extended confirmations and other responses that indicated a search for or negotiation of the meaning of the metaphors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Jaworska (2017) and Stampoulidis and Bolognesi (2019) identified metaphors using Metaphor Identification Procedure (MIP) guidelines without using any theoretical lens. The same goes with Skorczynska and Ahrens (2015), who used metaphor signaling and MIP guidelines to examine words and phrases metaphors in different genres.…”
Section: Figure 4 the Theoretical Lens Employed In The Analyzed Studiesmentioning
confidence: 98%
“…Across the 23 studies, 13 studies concentrated mainly on analyzing the word(s) or phrase(s) that could be the source domains of metaphor in a discourse Arab World English Journal www.awej.org ISSN: 2229-9327 521 or examining types of metaphors. For example, Skorczynska and Ahrens (2015) studied words and phrases which signal metaphors in the discourse of three different genres, i.e., U.S. presidential addresses, popular science articles, and business periodical articles. They found three metaphor signal categories through the analysis, i.e., copular similes, verbal processes, and modals/conditionals.…”
Section: Thematic Analysismentioning
confidence: 99%